Relevance of species-specific procalcitonin (PCT) and C-reactive protein (CRP) as clinical biomarkers in goat pneumonia - DEVI, SARITA; NAIR, AYUSHI S; MOHAPATRA, SUSHIL K; SINGH, RATN D; SUTHAR, ABHINAV N; PRAJAPATI, ANKIT S; PRAJAPATI, BHAVESH I; PATEL, RAMESH M (The Indian Journal of Animal Sciences, 2024)
Pneumonia is a leading cause of economic losses in the ruminant industry throughout the world. This study aimed to determine the relevance of species-specific procalcitonin (PCT) and C-reactive protein (CRP) as clinical biomarkers in goat pneumonia. Forty-six confirmed cases of goat pneumonia and 10 apparently healthy goats were included in this investigation. Detailed clinical examination involved recording of vital parameters in diseased as well as in apparently healthy goats. The level of PCT and CRP was analyzed in serum samples collected on day 0 and day 5 from all the 46 diseased goats and on day 0 from 10 healthy goats. A significantly higher pre-treatment concentrations of PCT (229.88±38.79 pg/mL) and CRP (44.13±2.72 µg/mL) in diseased goats was observed when compared with the control group. Significant positive correlation was found between PCT and CRP. Both PCT and CRP revealed a high level of discrimination between diseased goats and healthy ones (AUC= 1.0). Significant inhibition was observed in the values of PCT and CRP 5 days post-treatment in goats treated with two different antimicrobial drugs. Moreover, the obtained data showed a high degree of accuracy for both PCT and CRP in predicting the therapeutic response of infected goats at the selected thresholds (AUC = 1.0 and 1.0, respectively). Positive correlation between PCT and CRP with body temperature and heart rate was recorded. Measurement of PCT and CRP with clinical examination might be useful in assessing severity of goat pneumonia.